Exploring the locus of internal marketing. (19th May 2018) - Ozuem, Wilson; Limb, Natalie; Lancaster, Geoff
Abstract: Service and business-to-business companies have remained at the forefront of studies into internal marketing due to close contact between employees and customers. Marketing academics and practitioners have shown particular interest in the supermarket sector over recent years due to fluctuations in performance that have been reported. Consumers have negligible switching costs, so the risk of them purchasing substitute products is a problem to marketers where there is insignificant product differentiation. There is little evidence to support the benefits of internal market orientation in the food retail industry, and the main reason is difficulty of measuring its value. Although the UK food retail industry has been extensively researched, researchers have yet to address it properly in regard to internal market orientation. There is now an opportunity to create sustainable competitive advantage by providing a variety of offerings.